Web-Based Satisfaction Measurement System with Automated Index Computation and Role-Based Analytics - Ardiansyah; Muhammad Yafiz; Alma Vorfi Lama (Journal of Information Systems and Technology Research, 2026)
Measuring service satisfaction is essential for evaluating institutional performance; however, manual survey processes often cause delays in data compilation, duplicate entries, and limited analytical capability. This study aims to design and implement a web-based Satisfaction Measurement Information System that automates survey distribution, validation, index computation, and reporting. The system was developed using a structured system development methodology and implemented with modern web technologies that support centralized data management, automated index calculation, and role-based reporting. System evaluation was conducted through User Acceptance Testing (UAT) involving 45 respondents from 12 organizational units. The results show a UAT score of 88.6%, indicating high usability and functional suitability. In addition, the average data processing time was reduced from approximately five days (manual tabulation) to less than 10 minutes through automated computation. The system successfully managed 1,250 survey responses without duplicate records through validation mechanisms. These mechanisms and findings indicate that the proposed system improves the accuracy, processing speed, and accessibility of satisfaction data. This study contributes a practical model of automated satisfaction measurement with centralized analytics to support data-driven decision-making in higher education institutions